Kualitas Kehidupan Kerja Ditinjau dari Komitmen Karir dan Persepsi Gaya Kepemimpinan Transformasional - Azalea, Shita; Himam, Fathul (Universitas Islam Indonesia, 2014)
The purpose ofthis study is to examine the relationship between career commitment and employee's perception of transformational leadership to quality ofwork life. Data were collected from 70 employees from one company in Jakarta. Quantitative design was used and data was gathered using questionnaire according to each variables. Multiple regression analysis was applied to analyze the data. The result showed there are significant relationship between career commitment and employee's perception of transformational leadership to quality of work life with R = 0.685, p< 0,01. Total variance explained by career commitment and transformational to quality of work life was 46.9 percent.Keywords: quality of work life, career commitment, transformational leadership